(untitled) (Agroindustrial Science, 2025)
Ready-to-eat lettuces are highly demanded for salads but are exposed to factors that may pose health risks during production. There is an actual need to find alternatives to preserve fresh cut fruits and vegetables to improve the efficacy of the washing treatment. This study compared the antimicrobial effects of disinfection of raw ready-to-eat lettuce leaves with peracetic acid (CH3CO3H, PAA), sodium hypochlorite (NaClO) and washing with tap water. For disinfection, lettuce leaves were immersed in solutions of different concentration of PAA (40 and 80 ppm) and NaClO (100 and 150 ppm) for 2 min. The treated leaves were stored for 10 days under refrigeration (4 ºC). The aerobic plate count (APC), total coliforms, Salmonella spp. and total yeast and mold count (TYMC) were determined during this time. At the end of this period, samples treated with the lower PAA level had APC values like those obtained with both NaClO concentrations. The treatments with both disinfectants eliminated Salmonella spp., while the levels of APC, total coliforms and TYMC were below the limits of the Peruvian sanitary standard. It is concluded that PAA is a valid alternative to chlorine, and that higher concentrations could be used to achieve more significant population reductions.